Proxy topology building and routing in P2P SIP architectures - DAMIANI, Ernesto; HOUNGUE, Yénukunmè Pélagie Elyse (My University, 2010)
Research activities have recently begun on the integration of Peer-to-Peer (P2P) principles into the Session Initiation Protocol (SIP). We have contributed to these activities by proposing a P2P SIP architecture where the SIP location service is not managed by the P2P overlay but integrated in proxies that run over peer entities in the P2P overlay. Having SIP proxies as first-class entities, raises two important issues: proxy topology building and proxy-level routing. Thanks to proxy topology building, a proxy joining the P2P overlay knows where it should insert itself in the network of proxies. Proxy-level routing enables messages to be routed in the SIP network built by proxy topology building. This paper proposes a novel framework for proxy topology building and proxy-level routing. The framework is general enough to be used on any P2P overlay that meets a minimal set of requirements. Independence from the P2P infrastructure is aimed at supporting seamless integration of multiple SIP communication environments. Our framework relies on an algorithm that builds the network of proxies in a ring and uses its own routing algorithm to route calls. We describe our novel routing algorithm used between proxies on the ring and evaluate its performance through simulation.
Keywords: P2PSIP